Development of Information and Management System of Student Competition Groups through User-Centered Design Approach - Dinan Yulianto; Ahmad Raditya Cahya Baswara; Lugas Alhawariy; Marina Indah Prasasti; Gema Antika Hariadi (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2023)
The majority of universities in Indonesia make maximum efforts to participate and excel in the implementation of the Student Creativity Program (namely: PKM). PKM requires students to collaborate interdisciplinary or multidisciplinary. The problem at the beginning of PKM implementation is establishing groups, where students find it difficult to have fellow students or supervisors from different disciplines in groups and according to the topic of their PKM. This research develops a user-oriented interaction and interface of information systems and group management. Development was carried out through a User-Centered Design which consisted of the following stages: plan the human-centered process; understand and specify the context of use; specify the user requirements; produce design solutions to meet user requirements; and evaluate the design against the requirements. Testing using System Usability Scale (SUS) and User Experience Questionnaire (UEQ) approach were conducted on 30 respondents who had competencies as business analysts, programmers, and testers. The results of the mean score of the SUS test are 80, and the mean Score of the UEQ test on the Attractiveness variable is 1.922, Clarity is 2.158, Efficiency is 2.042, Accuracy is 1.708, Stimulation is 1.967, and Novelty is 1.917. The system has achieved the goals and user experience because all the testing scores are above the standard provisions.